Literature Review: Hubungan Kelembaban Rumah dengan Kejadian Pneumonia pada Balita di Wilayah Pabrik - Gravita Piranti Kusumo; Farida Heriyani; Nurul Hidayah (Homeostasis, 2021)
Abstract: Pneumonia can be the world's leading cause of death in toddlers. According to who in 2017 child deaths caused by pneumonia as many as 808,694 children. High house humidity and pollutants coming from the factory can be the factors. The purpose this literature review summarizes and analyzes the relationship between humidity and incidence pneumoniae in toddlers around factory area. Literature review method is narrative review using Indonesian journal. Search databases using PubMed, Garuda, Cochrane library and Google Scholar. 20 articles are included in this literature review with a publication time of 10 years. Based on the articles analyzed, 11 (73.33%) results were obtained the article states humidity relations with incidence pneumonia in toddlers. Then, 4 (80%) results were obtained article there is a relationship of factory pollutants with pneumonia in toddlers. The results analysis were obtained 1 (33.33%) article with p value= 0,000 is a relation with humidity pneumonia incidence of toddlers living around the factory. Keywords: house humidity, pneumoniae in toddlers, factory pollution Abstrak: Pneumonia dapat menjadi penyebab kematian di dunia pada balita. Menurut WHO tahun 2017 kematian anak disebabkan oleh pneumonia sebanyak 808.694 anak. Kelembaban rumah tinggi dan polutan yang berasal dari pabrik dapat menjadi salah satu faktornya. Tujuan literature review ini merangkum dan menganalisis hubungan kelembaban balita di area pabrik dengan kejadian pneumonia. Metode literature review ini adalah narrative review menggunakan jurnal bahasa Indonesia. Pencarian database menggunakan PubMed, Garuda, Cochrane library dan Google Scholar. 20 artikel disertakan pada literature review ini dengan waktu publikasi 10 tahun. Berdasarkan artikel yang dianalisis didapatkan hasil 11 (73,33%) artikel menyatakan kelembaban balita berhubungan dengan kejadian pneumonia. Kemudian, didapatkan hasil 4 (80%) artikel terdapat hubungan polutan pabrik terhadap kejadian pneumonia pada anak balita. Hasil analisis didapatkan 1 (33,33%) artikel dengan nilai-p = 0,000 terdapat hubungan kelembaban balita dengan kejadian pneumonia di sekitar pabrik. Kata-kata kunci: kelembaban rumah, pneumonia pada balita, polutan pabrik